Vernacular traditions in Norwegian jewelry design - Past, present, future - Skjerven, Astrid (FormAkademisk, 2015)
Living in an era of globalization, the capability of communicating identity has become of greater importance than ever. This has increased our estimation of the vernacular, which represents an expression of a national or local identity. In Norway the vernacular tradition in silver jewelry is particularly strong. It has played an important role not only locally, but also in the constantly changing relation with the outside world, in accordance with the societal situation. It should therefore constitute a reliable indicator of how our country relates to the present process of globalization. The aim of the paper is to throw light on the relation between Norway’s role on the global scene and the use of the vernacular tradition in the development of jewelry design in general. It consists of a historical exploration that leads up to a discussion the present and future situation. Today there is a cleft between consumer behavior and avant-garde practice. In accordance with the global situation and Norway’s geopolitical situation of existing in the outskirts of political and economic decisions, the situation is characterized by a variety of practices, and by a slow acceptance of the vernacular values in the world of avant-garde practitioners.